2017
DOI: 10.1093/protein/gzw081
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization ofBacillus circulansxylanase by combinatorial insertional fusion to a thermophilic host protein

Abstract: High thermostability of an enzyme is critical for its industrial application. While many engineering approaches such as mutagenesis have enhanced enzyme thermostability, they often suffer from reduced enzymatic activity. A thermally stabilized enzyme with unchanged amino acids is preferable for subsequent functional evolution necessary to address other important industrial needs. In the research presented here, we applied insertional fusion to a thermophilic maltodextrin-binding protein from Pyrococcus furiosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Kinetic stability is related to the timescale over which an enzyme remains active . Wild‐type BCX was found to lose xylanase activity during incubation (Figure A) . Less than 5 % of the original xylanase activity of wild‐type BCX was detected after 14 days′ incubation.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Kinetic stability is related to the timescale over which an enzyme remains active . Wild‐type BCX was found to lose xylanase activity during incubation (Figure A) . Less than 5 % of the original xylanase activity of wild‐type BCX was detected after 14 days′ incubation.…”
Section: Resultssupporting
confidence: 89%
“…The DNA coding for the resulting BCX variant was referred to as bcx‐klvfwak . For the PCR, a plasmid pET23b‐BCX, in which DNA encoding BCX was cloned, was used as a template. The PCR was carried out with 5′‐TATCT TCATA TGCAC CACCA CCACC ACCAC GCCTC CACAG ACTAC TGGCA AAA‐3′ and 5′‐AATGT ATAAC TAGTT TATCA TTTCG CCCAA AACAC CAGTT TGCCA CCGCC CCACA CTGTA ACGTT GGAAG AACCA G‐3′ as forward and reverse primers, respectively; the NdeI restriction enzyme site at the 5′‐end and the SpeI restriction enzyme site at the 3′‐end of bcx‐klvfwak are underlined.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, a series of studies performed by Kim and coworkers demonstrated that domain insertion of a guest protein may benefit from high thermostability of a host protein [38,39,40,41]. Insertional fusion has recently been highlighted as a novel means of creating multi-domain protein complexes, where functionalities are often integrated and coupled with each other.…”
Section: Thermophilic Proteins As a Scaffold For Functional Evolutionmentioning
confidence: 99%